Efeitos do fogo sobre os mamíferos de médio e grande porte na TI Kadiwéu, Porto Murtinho, Mato Grosso do Sul - ANNY DE MORAES COSTA (2022)
Indigenous lands have a tradition of management with the use of fire, however, wildfires or burning at inappropriate time can be harmful to the environment. In this study, the influence of fire regimes on the community of medium and large mammals in the Indigenous Land (TI) Kadiwéu, in Porto Murtinho/MS was evaluated. Therefore, the landscape was classified into 4 sampling treatments considering frequency (high or low) and last period of burning (early or modal-late). Trap cameras and active search for mammals around the cameras were used. The treatments were compared in relation to the composition, richness and abundance of mammal species and the composition of the landscape. In total, 21 species of medium and large mammals were recorded. The composition, richness and abundance of species did not differ significantly between treatments or in relation to differences in landscape composition. The species recorded are widely distributed across all phytophysiognomies of the study area, occurring in all types of burned areas, with no apparent selection of species by any type of area. With this, we conclude that different fire regimes combined with the differences in the composition of the landscape, are not determining factors in the structure of the community of medium and large mammals in the Kadwéu TI, since the species were present in most treatments. Finally, the importance of the area for the conservation and preservation of species is highlighted, being fundamental for the maintenance of regional biodiversity, as it has a great local diversity, including endangered species, which are adapted to different fire regimes.